FAIR MINORITY SHAREHOLDING PERCENTAGE DETERMINATION FORMULATION AND PROVIDING LEGAL PROTECTION FOR MINORITY SHAREHOLDERS - Widjaja A.; Budiono A.R.; Sihabudin; Hamidah S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Law Number 40 of 2007 concerning Limited Companies has stipulated that the minimum percentage limit for minority shareholding is 10%. This limit causes justice and legal protection for minority shareholders to be neglected. This article aims to discuss the formulation of determining the minimum percentage of minority shareholding that provides justice and legal protection for minority shareholders in future changes to the law. The method used is a normative legal research method with a statute approach and a conceptual approach. The results obtained are the idea of changing the law in the future, namely the formulation of determining the percentage of minority shareholding can use the economies of scale of a Limited Company by using an indicator of the amount of paid-in capital, with this arrangement it is expected to provide justice and legal protection for minority shareholders.